LOCAL COMMUNITY ATTITUDES TOWARD SUSTAINABLE RURAL TOURISM CASE STUDY OF NUSATOURISM VILLAGE IN ACEH - Yahya, Afrida; Fang, Jane Teng Yan (PEOPLE: International Journal of Social Sciences, 2019)
Studies related to sustainable rural tourism have been attracting researcher interest due to the many benefits it provides for not only host community but also for all stakeholders of rural tourism such as tourists, tour operators and tourism business managers. The aim of this study is to understand the attitudes of local community in improving rural tourism sutainability in Aceh. The study employs qualitative research design and utilized the insightful case study approach to comprehend the issues of local community attitudes on sustainable rural tourism. Particularly, the intrinsic case study is chosen to explore the study because Nusa tourism village has been successfully practicing rural tourism business and becomes the fastest growing tourism village in Aceh. In addition Nusa tourism village also can become a role model for other tourism villages in Aceh for it unique qualities and supports of it local leaders and communities, also the strong positive impact its provide for local community. This study will construct practical knowledge that can be applied throughout tourism villages with the same level of requirements and situations.